Lecciones éticas y ciudadanas de los Pueblos Mayas para el mundo. Filosofía política y metodologías de un proyecto educador - Bertely, María (Revista de Antropología Social, 2007)
This article describes some of the results of the project entitled “Intercultural conflict, education and active democracy in Mexico: Citizenship and indigenous rights in the bilingual and intercultural pedagogical movement of the Los Altos, Northern and Lacandon Rainforest Regions of Chiapas”. The first part describes the context in which this project was developed, the political philosophy that inspired it, as well as the methodology used, with particular emphasis on: (1) domination-subordination in intercultural relations; (2) the implicit expressions of a praxis of active resistance in the practical lives of indigenous societies, and (3) the various approaches applied, viz. inductive (Gasché, forthcoming a & b), qualitative (Glasser and Strauss, 1967), ethnographic (Bertely, 2000a), and evocative (Podestá, 2002 y 2003; Lindenberg, 1996). The second part of the article systematizes the results of the experimental stage and that devoted to the design of the educational material within a project founded on a mutual learning process and collaboration between indigenous teachers and non-indigenous specialists.